Agronomical evaluation and chemical characterization of Linum usitatissimum L. as oilseed crop for bio-based products in two environments of Central and Northern Italy - Tavarini, Silvia; Angelini, Luciana G.; Casadei, Nerio; Spugnoli, Paolo; Lazzeri, Luca (Italian Journal of Agronomy, 2016)
In the recent years, new perspectives for linseed (Linum usitatissimum L.) are open as renewable raw material for bio-based products (Bb), due to its oil composition, and the interesting amounts of coproducts (lignocellulosic biomass). Therefore, the possibility to introduce linseed crop in two environments of central and northern Italy, traditionally devoted to cereal cultivation, has been evaluated. Twoyears field trials were carried out in the coastal plain of Pisa (Tuscany region) and in the Po valley (Bologna, Emilia Romagna region), comparing two linseed varieties (Sideral and Buenos Aires). Agronomical evaluation (yield and yield components), seed and oil characterization (oil, protein content, and fatty acid composition), together with carbon (C) and nitrogen (N) content of the residual lignocellulosic biomass were investigated. The two varieties, grown as autumn crop, showed a different percentage of plant survival at the end of winter, with Sideral most resistant to cold. The achieved results showed significant influence of cultivar, location and growing season on yield and yield components, as well as on chemical biomass composition. In particular, Sideral appeared to be the most suitable variety for tested environments, since higher seed yield (3.05 t haâ€“1 as mean value over years and locations) and above-ground biomass (6.98 t haâ€“1 as mean value over years and locations) were recorded in comparison with those detected for Buenos Aires (1.93 and 4.48 t haâ€“1Â of seed production and lignocellulosic biomass, respectively). Interestingly, in the northern area, during the 1st year, Buenos Aires was the most productive, despite its low plant survival at the end of winter, which determined a strong reduction in plant density and size. In such conditions, the plants produced a larger number of capsules and, consequently, high seed yield (3.18 t haâ€“1). Relevant differences were also observed between the two years, due to the variability of climatic characteristics (temperature levels, and moisture regimes). All these findings confirmed as, in linseed, yield and yield components are quantitatively inherited and influenced by both genotype and environment (location and climate). Varietal and environmental effects were also recorded for oil content and yield, and, generally, good oil percentages, for both genotypes, were found (ranging from 44 to 49% on dry matter basis). Oil from the two varieties was characterized by a stable proportion of polyunsaturated fatty acids with a high content of alpha-linolenic acid (more than 57%), that makes this oil suitable to be used in paints, resins, varnishes, linoleum, polymers and oleochemicals. Finally, our results pointed out as above- and below-ground biomasses, were different in terms of quantity, and chemical characteristics (N, C and C/N ratio). Interesting amounts of N and C could return into the soil by crop residues (stem portions and roots), thus underling the possibility to maintain and/or increase the soil organic matter pool.